Reproducibility of blood lactate concentration rate under isokinetic force loads - Nitzsche. N.; Baumgärtel, L.; Maiwald, C.; Schulz, H. (Sports, 2018)
(1) Background: Maximum isokinetic force loads show strongly increased post-load lactate concentrations and an increase in the maximum blood lactate concentration rate ( VLamax), depending on load duration. The reproducibility of V Lamax must be known to be able to better assess training-related adjustments of anaerobic performance using isokinetic force tests. (2) Methods: 32 subjects were assigned to two groups and completed two unilateral isokinetic force tests (210° s-1, Range of Motion 90°) within seven days. Group 1 (n = 16; age 24.0 ± 2.8 years, BMI 23.5 ± 2.6 kg m-2, training duration: 4.5 ± 2.4 h week-1) completed eight repetitions and group 2 (n = 16; age 23.7 ± 1.9 years, BMI 24.6 ± 2.4 kg m-2, training duration: 5.5 ± 2.1 h week-1) completed 16 repetitions. To determine V Lamax, capillary blood (20 µL) was taken before and immediately after loading, and up to the 9th minute post-load. Reproducibility and variability was determined using Pearson and Spearman correlation analyses, and variability were determined using within-subject standard deviation (Sw) and Limits of Agreement (LoA) using Bland Altman plots. (3) Results: The correlation of V Lamax in group 1 was r = 0.721, and in group 2 r = 0.677. The Sw of V? Lamax was 0.04 mmol L-1 s-1 in both groups. In group 1, V Lamax showed a systematic bias due to measurement repetition of 0.02 mmol L-1 s-1 in an interval (LoA) of ±0.11 mmol L-1 s-1. In group 2, a systematic bias of -0.008 mmol L-1 s-1 at an interval (LoA) of ±0.11 mmol L-1 s-1 was observed for repeated measurements of VLamax. (4) Conclusions: Based on the existing variability, a reliable calculation of V Lamax seems to be possible with both short and longer isokinetic force loads. Changes in V Lamax above 0.11 mmol L-1 s-1 due to training can be described as a non-random increase or decrease in VLamax